Apuntes de Calculo Vectorial - Belauzarán García, Eduardo; Frontana de la Cruz, Bernardo; Gomez Saavedra, Ricardo; González Gutierréz, Enrique; Patiño Ramírez, Jesús Antonio; Rivas Gómez, Santiago; Mendoza Márquez José Antonio (Facultad de Ingeniería, 1981)
Apuntes de calculo vectorial
Apuntes de calculo vectorial
Keywords: calculo; vectorial; Apuntes